Guidance for the Independent External Evaluation of CGIAR Research Programs (CRPs) - CGIAR Independent Evaluation Arrangement (CGIAR Independent Evaluation Arrangement, 2015)
This Guidance Note is intended as helpful reference for those commissioning and carrying out CRP evaluations.